Chitin and chitosan from shellfish waste and their applications in agriculture and biotechnology industries - Sampurna Rai; Prashant Pokhrel; Pranaya Udash; Menjo Chemjong; Namita Bhattarai; Arthittaya Thuanthong; Sitthipong Nalinanon; Nilesh Nirmal (My University, 2025)
A shellfish processing plant generates only 30–40% of edible meat, while 70–60% of portions are considered inedible or by-products. This large amount of byproduct or shellfish processing waste contains 20–40% chitin, that can be extracted using chemical or greener alternative extraction technologies. Chitin and its derivative (chitosan) are natural polysaccharides with nontoxicity, biocompatible, and biodegradable properties. Due to their versatile physicochemical, mechanical, and various bioactivities, these compounds find applications in various industries, including: biomedical, dental, cosmetics, food, textiles, agriculture, and biotechnology. In the agricultural sector, these compounds have been reported to promote: plant growth, plant defense system, slow release of nutrients in fertilizer, plant nutrition, and remediate soil conditions, etc. Whereas, biotechnology applications indicated: enhanced enzyme stability and efficacy, water purification and remediation, application in fuel cells and supercapacitors for energy conversion, acting as a catalyst in chemical synthesis, etc. This review provides a comprehensive discussion on the utilization of these biopolymers in agriculture (fertilizer, seed coating, soil treatment, and bioremediation) and biotechnology (enzyme immobilization, energy conversion, wastewater treatment, and chemical synthesis). Additionally, various extraction techniques including conventional and non-thermal techniques have been reported. Lastly, concluding remarks and future direction have been provided.
Keywords: Nanocomposite Films for Food Packaging